2008
DOI: 10.1177/1049732307308979
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Processes and Qualities of Spiritual Nursing Care

Abstract: Although the importance of spiritual care is widely recognized in nursing theory, recent research suggests that it is rarely attended to in nursing practice. One explanation for this contradiction is the conceptual confusion that exists regarding the meaning of spiritual nursing care. To help unravel this confusion, in-depth open-ended interviews were conducted in an oncology care setting with 29 individuals representing the multiple perspectives of nurses, patients, family, and others. Phenomenological analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 49 publications
2
46
0
2
Order By: Relevance
“…). The characteristics of this relationship are as follows: ‘creation and promotion of confidence in relationship’ (Tanyi ); ‘establishment of professional boundaries in relationship’ (Puchalski & Ferrell ); ‘transference of healing energy form nurse to patient’ (Carr ); ‘honesty in relationship’, ‘use of useful communication skills’; ‘establishment of eye contact’ (McSherry ); ‘attention to the power of speech in the promotion of healing’ (Carson & Koenig ); and ‘showing sensitivity to patients’ non‐verbal signals’ (Rieg et al. ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…). The characteristics of this relationship are as follows: ‘creation and promotion of confidence in relationship’ (Tanyi ); ‘establishment of professional boundaries in relationship’ (Puchalski & Ferrell ); ‘transference of healing energy form nurse to patient’ (Carr ); ‘honesty in relationship’, ‘use of useful communication skills’; ‘establishment of eye contact’ (McSherry ); ‘attention to the power of speech in the promotion of healing’ (Carson & Koenig ); and ‘showing sensitivity to patients’ non‐verbal signals’ (Rieg et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, nurse's professional commitment (Carson & Koenig ), professional responsibility and accountability (Chan et al. ), professional competency (Carr ), accurate sensory perception (Clark et al. ; Ross ) and ability to understand and accept others’ feelings and behaviours are among the essential prerequisites for the fulfilment of patients’ spiritual needs.…”
Section: Identifying the Antecedents And Consequences Of The Conceptmentioning
confidence: 99%
See 1 more Smart Citation
“…, Como , Koenig ). Carr () suggested that spiritual care is about developing caring relationships that promote spiritual well‐being. According to Narayanasamy (), nurses can collect data about the patient's spiritual well‐being by assessing areas such as the patient's source of strength and hope, sense of meaning and purpose, self‐esteem, anxiety and anger.…”
Section: Introductionmentioning
confidence: 99%
“…It has been described as a whole and natural experience, which is often unplanned and sometimes even unrecognized by either the nurse or the person being cared for (Carr, 2008;Carroll, 2001). Critical to spiritual care is that the carer approach his or her work with receptivity.…”
mentioning
confidence: 98%